1985
DOI: 10.1136/jcp.38.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Study of discrepancies in rubella haemagglutinin titrations and a reappraisal of diluents used in the rubella haemagglutination inhibition technique.

Abstract: SUMMARY To elucidate inconsistencies in rubella haemagglutinin assays the components of the assay technique were examined. The results of carefully controlled assays of rubella haemagglutinin antigens from different sources ih various plates and diluents with four species of indicator cells are reported. The quality and quantity of gelatin in the dextrose-gelatin-veronal buffered diluent commonly used in rubella haemagglutinin assays had a profound effect on the haemagglutination pattern and antigen titre. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…per ml [24]. In 1985 Murray, Stanton and Gardner [25] showed that much of the variation was due to the presence of gelatin in the special veronal buffer. They recommended using ordinary CFT buffer with the addition of 02 % albumen which gave higher haemagglutinin titres.…”
Section: Diagnosis Of Acquired Rubellamentioning
confidence: 99%
“…per ml [24]. In 1985 Murray, Stanton and Gardner [25] showed that much of the variation was due to the presence of gelatin in the special veronal buffer. They recommended using ordinary CFT buffer with the addition of 02 % albumen which gave higher haemagglutinin titres.…”
Section: Diagnosis Of Acquired Rubellamentioning
confidence: 99%